2017
DOI: 10.1186/s12967-017-1189-5
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of necroptotic proteins in failing human hearts

Abstract: BackgroundCell loss and subsequent deterioration of contractile function are hallmarks of chronic heart failure (HF). While apoptosis has been investigated as a participant in the progression of HF, it is unlikely that it accounts for the total amount of non-functional tissue. In addition, there is evidence for the presence of necrotic cardiomyocytes in HF. Therefore, the objective of this study was to investigate the necroptotic proteins regulating necroptosis, a form of programmed necrosis, and thereby asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 33 publications
3
72
2
Order By: Relevance
“…The terms associated with cell deathapoptosis and anoikisare listed, but the terms necrosis and necroptosis, as a form of programmed necrosis (Szobi et al 2017), are missing.…”
Section: Missing Important Cytological Termsmentioning
confidence: 99%
“…The terms associated with cell deathapoptosis and anoikisare listed, but the terms necrosis and necroptosis, as a form of programmed necrosis (Szobi et al 2017), are missing.…”
Section: Missing Important Cytological Termsmentioning
confidence: 99%
“…In the permanent myocardial ischaemia animal model, RIP3 knockout would decrease the inflammatory response and hypertrophic growth of the cells while the ejection fraction was increased 60. It had been also observed that the markers of necrosis, phospho‐MLKL, are also up regulated in the end‐stage heart failure patients 71. Until now, several important factors which are involved in the regulation of death receptor‐mediated necrosis in the pathogenesis of heart patients have been revealed.…”
Section: Necrosis In Heart Diseasesmentioning
confidence: 99%
“…60 It had been also observed that the markers of necrosis, phospho-MLKL, are also up regulated in the end-stage heart failure patients. 71 Until now, several important factors which are involved in the regulation of death receptor-mediated necrosis in the pathogenesis of heart patients have been revealed.…”
Section: Death Receptor-mediated Necrosis In Heart Diseasesmentioning
confidence: 99%
“…Findings from analyzing biochemical markers of necroptosis in the myocardium of humans with end-stage heart failure resulting from myocardial infarction (MI) or dilated cardiomyopathy indicate an involvement of necroptosis in the development of heart failure. 20 A genetic variant in the RIPK3 promoter region associated with increased RIPK3 transcription may contribute to the poor prognosis of heart failure patients. 21 Animal experiments demonstrated an important role for necroptosis in post-MI remodeling, 22 myocardial ischemia/reperfusion (I/R) injury, cardiotoxicity of doxorubicin treatment, 23, 24 and paraquat-induced cardiac contractile dysfunction.…”
Section: Introductionmentioning
confidence: 99%